Pelaksanaan Pendidikan Karakter Di Lingkungan Sekolah Sebagai Upaya Membentuk Pondasi Moral Generasi Penerus Bangsa - Sri Armini, Ni Nengah (Metta : Jurnal Ilmu Multidisiplin, 2024)
Character education has become a major focus in helping students to develop strong moral principles and ethical values. This research examines the strategies and methods used in character education to build students' strong character. The study covers important concepts such as the concept of character education, its purpose, the teacher's role in the classroom, and how to make the relationship between teachers and students as transparent as possible. A deep review of the positive lessons in character education was also conducted to ensure that character education can be implemented successfully. The development of an integrated curriculum, schools' and teachers' roles in implementing the characteristics of education, as well as character building in a learning activity, are examined. In addition, this research focuses on some aspects that are required for implementing character education in the school, such as fostering a positive school culture. The purpose of this study is to examine how the character education can significantly improve students' moral development through the experience of a positive school environment. This research is part of a qualitative research type. The method used in this research is literature review. This paper focuses on the positive outcomes, growth and achievements of character-based education by analyzing empirical data and new research findings. The role of teachers as mentors and guides is crucial in developing students' character. Through a better understanding of effective strategies and potential barriers, this research offers valuable contributions to the development of more effective teaching methods in the future. The main focus of this research is the importance of the teacher's role in implementing character education.